2006
DOI: 10.1097/01.wnr.0000220133.32091.d6
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to MK801 induces structural reorganization of the central nervous system

Abstract: Schizophrenia, a progressive disorder displaying widespread pathological changes, is associated with the loss of glutamatergic function and selective loss of cytoskeletal proteins, such as MAP2, in regions severely affected by this disease. As schizophrenia is associated with perinatal brain trauma, we monitored changes in several functionally different proteins following injury-promoting MK801 blockade of N-methyl-D-aspartate receptors in neonatal rats. Within the somatosensory cortex, MK801 triggered robust,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Previous studies have shown this region (specifically layers IV and V) is especially sensitive to NMDAR blockade at this age and that AC3 induction peaks at 8-16 hours (Lema Tomé et al, 2006, Turner et al, 2007b, Turner et al, 2009a). For ease of comparison, we remained focused on this region (and these layers) in the present study.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies have shown this region (specifically layers IV and V) is especially sensitive to NMDAR blockade at this age and that AC3 induction peaks at 8-16 hours (Lema Tomé et al, 2006, Turner et al, 2007b, Turner et al, 2009a). For ease of comparison, we remained focused on this region (and these layers) in the present study.…”
Section: Resultsmentioning
confidence: 70%
“…However, we and others have clearly demonstrated that age-dependent injury is to be expected following exposure to such agents (Ikonomidou et al, 1999a, Turner et al, 2002). We have explained this enigmatic outcome using a Calcium Set Point hypothesis (Turner et al, 2002, Lema Tomé et al, 2006, Turner et al, 2007a, Turner et al, 2007b, Ringler et al, 2008, Turner et al, 2009a). Briefly, immature neurons unable to buffer abrupt changes in calcium are vulnerable to such changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, at P21, agents that block this receptor no longer promote cell death. Numerous mechanisms have been proposed for this age-dependent injury such as loss of neuronal calcium [1012], disruption of synaptic circuitry, up-regulation of NMDAR protein or absence of trophic support [1,8,9,13,14]. …”
mentioning
confidence: 99%
“…For example, the somatosensory cortex (S1) and layer II of primary and secondary motor cortex (M1 and M2) are regions susceptible to age-dependent MK801-induced apoptosis (Lema Tomé et al, 2006a; Lema Tomé, Nottingham, Smith, Beauchamp, Leung, & Turner, 2006b; Turner et al, 2007b). The neuronal populations found in these regions include both pyramidal and non-pyramidal cells that are immunoreactive for CaBPs (Alcantara, Ferrer, & Soriano, 1993; Alcantara, Soriano, & Ferrer, 1996; Celio, 1990; Conde, Lund, Jacobowitz, Baimbridge, & Lewis, 1994; de Lecea, del Rio, & Soriano, 1995).…”
mentioning
confidence: 99%